Odin på træet - Schjødt, Jens Peter (Religionsvidenskabeligt Tidsskrift, 1995)
The Norse myth of Odin who dangled from the world tree during nine nights has aroused much discussion among scholars as to whether the god is being initiated or sacrificed. After having discussed the arguments, the article proceeds by analysing the two phenomenological categories of sacrifice and initiation and some of the driterias we may use in order to make a distinction. It is concluded that the main difference is the relation between subject and object. Speaking about sacrifice there is no identity between these, whereas identity is exactly what characterizes initiation. In a way initiation may be termed "self sacrifice" - a term, however, which should not be recommended in order to avoid confusion. Thus, even though the symbolism of the two phenomena is much alike, it seems most reasonable to designate the myth of Odin on the tree as an initiation.